Temperature-dependent electrical transport, Hall effect, and Seebeck properties of bulk chemically reduced graphene oxide with bipolar charge carrier materials - Keerati Maneesai; Kanyapak Silakaew; Sunisar Khammahong; Chaiwat Phrompet; Chaval Sriwong; Chanchana Thanachayanont; Chesta Ruttanapun (AIP Advances, 2023)
The temperature-dependent electrical transport, Hall effect, and Seebeck properties of bulk-reduced graphene oxide (rGO) prepared by a chemical reduction process were investigated in a temperature range of 310–475 K. The bulk rGO contained bipolar charge carriers with p-type to n-type switching at a temperature of 420 K. The materials illustrated a p-type characteristic in the temperature range of 310–420 K and n-type characteristic in the temperature range of 420–475 K. The charge transport mechanism was that of the graphene-derived 2D material in the p-type regime and governed by polaronic charge carriers.
Keywords: Graphene research and applications; Advancements in Battery Materials; Quantum and electron transport phenomena